Characterization Of Electrical Properties Of Graphene-Based Materials On Mems Structures - Brodský, Jan (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
This work presents characterization of basic electrical properties of graphene and graphene oxide. Graphene was prepared by chemical reduction of graphene oxide. The experimental part of this work describes the process of graphene oxide and reduced graphene oxide sample preparation and measurement of its current-voltage characteristic by two-point probe method. Measurement is carried out on MEMS structure, which can be used for mechanical bending. Such structure will serve for utilization of graphene and other 2D materials.
Keywords: MEMS; graphene; graphene oxide; current-voltage characteristic; Raman spectroscopy